Isolation and screening of lactic acid bacteria from grasshopper gut as novel probiotic candidates to digest cellulose polymer. (May 2019) - Abdullah, R; Erfianti, T; Pratama, D A; Wijanarka,
Abstract: The nutritional needs are the primer need in the earth. Various solution of food security problem such as GMO product and chemical fertilizer, are still not effective to clear it because the global warming annualy reported may cause to the crop failures. In addition, the amount of carbohydrate that can be adsorbed by human body is less. The Cellulose is one of the carbohydrate that human can not adsorb to get glucose. Grasshopper can digest the cellulose of grass because there are bacteria live in their organs to produce the enzyme. The bacteria that have an ability giving advantage in the body are known as probiotic. However, the development of this function has became a great attention. The aim is obtaining grasshopper gut bacteria caracterized as lactic acid bacteria potential as novel probiotic to produce cellulase for human digestion. Methods used are; Isolation of grasshopper gut bacteria, Purification and screening modificated of novel probotic candidates. The bacteria were screened by using modificated medium to detect the enzyme activity and pathogenic possibility as well as SP-SDS method to enumerate the tolerance of the bacteria after treatment in the period. The result shows that two bacteria strains of grasshopper gut bacteria are capable to break down the cellulose in the screening process. The bacteria was also caracterized as the lactid acid bacteria. The activity of gamma haemolytic of the bacteria shows the non-pathogenic property on blood. Bile salt and acid pH condition for 48 hour period was tested on the bacteria shows the high tolerance of life in the digestion. In conclusion, there are strain of grasshopper gut bacteria can be used as novel probiotic candidate to digest cellulose as solution of food security.